2008
DOI: 10.1520/jai101312
|View full text |Cite
|
Sign up to set email alerts
|

A New Model to Predict the Oxidation Kinetics of Zirconium Alloys in a Pressurized Water Reactor

Abstract: The previous CEA corrosion code COCHISE provided satisfactory simulations of in-reactor corrosion of the fuel cladding when used in its validity range. In contrast, it could lead to hazardous predictions if applied out of this range due to the strongly linked parameters mainly based on the analysis of French pressurized water reactor (PWR) data. To predict the oxidation kinetics for new operating conditions or new materials, the CEA and EDF decided to develop a new model, named CORCY, which is based on a more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…However, it was recently shown that the ion irradiation of the metal/oxide interface results in a significant increase of the oxidation rate of the Zircaloy-4 alloy by increasing the vacancy concentration gradient. The accelerating factor (∼2) is close to that measured between cladding corroded in autoclave and in PWR at low burnup [3,17].…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…However, it was recently shown that the ion irradiation of the metal/oxide interface results in a significant increase of the oxidation rate of the Zircaloy-4 alloy by increasing the vacancy concentration gradient. The accelerating factor (∼2) is close to that measured between cladding corroded in autoclave and in PWR at low burnup [3,17].…”
Section: Introductionsupporting
confidence: 76%
“…Four major assumptions are proposed in the literature in order to explain this acceleration [2,3]. The first one is that the hydrides precipitated beneath the metal/oxide interface in the metallic part of the cladding, resulting from the hydrogen uptake by the matrix, may be corroding at a faster rate than the metal itself [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the exponent m can lie between the limiting cases 0.5 < m < 1. A similar expression is used in the model in [3]. Fig.…”
Section: Expression (3) Is a Stationary Solution Of The Equation For mentioning
confidence: 99%
“…The engineering model was constructed using an approach similar to foreign models [2,3]. The stages of oxidation before and after the turning point are examined.…”
mentioning
confidence: 99%
See 1 more Smart Citation